Alterações ultrassonográficas na pancreatite aguda canina - Ueda, Mariana Yukari [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Pancreatitis is a predominantly disease of the exocrine pancreas, which occurs commonly in dogs. Acute pandreatitis is reversible, with the removal of the primary cause, whereas chronic pancreatitits is irreversible, with histopathological changes, such as atrophy and fibosis that occurs from persistent inflammation. In dogs, clinicl signs ranging among abdominal pain and anorexia until potential insufficiency of various organs and Disseminated Intravascular Coagulation. In general, dogs with acute illness presents vomiting, anorexia, abdominal pain and several degrees of dehydration, collapse and shock. The caim of this monograph is evaluate ultrassound changes in dogs with panceatitis. Ultrassound is a valuable technique to evaluate exocrine pancreas, with association with another diagnostic modalities will be able to increase the preciosion of the diagnosis

Pancreatite é uma doença predominantemente do pâncreas exócrino, que ocorre comumente em cães. A pancreatite aguda é reversível, com a remoção da causa primária, enquanto que a pancreatite crônica é reversível e presenta alterações histopatológicas como atrofia e fibrose. Os sinais clínicos variam de acordo com a gravidade da doença, desde dor abdominal discreta e anorexia até um quadro final de abdômen agudo, de insuficiência potencial de vários órgãos e coagulação vascular disseminada (CID) em uma fase terminal. O objetivo desta monografia é de abordar as principaos manifestações ultrassonográficas em cães com pancreatite. Uma vez que a ultrassonografia é uma énica valiosa para avaliação do pâncreas exócrino que, em associação com outras modalidades diagnósticas, poderá aumentar a precisão do diagnóstico da doença
Keywords: Cão - Doenças; Pancreatite; Ultrassonografia veterinária; Pancreatitis; Canine